Trial of Square and Round Edge Intraocular Lens on Preventing Posterior Capsule Opacification - Chowdhury, PK D (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 51-52 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12544